Derivatisation of 2,4 (dinitrophenyl hydrazine) DNPH in Canola oil oxidation - Marini Damanik; Michael Murkovic (Universitas Negeri Medan, 2019)
Lipid oxidation during heating started at the allylic position of the double bond of unsaturated fatty acids. Primary lipid oxidation which was produced during heating are generally unstable and directly decompose into secondary oxidation products. The oxidative and thermal stability of Rapeseed oil was evaluated using Rancimat 679. Oil samples were heated at 120oC for 10 hours which are taken started from 5, 6, 6.5, 7, 7.5, 8, 9 and 10 hours. Derivatization with DNPH eluted with a mixture of methanol (60%) and water (40%). The aldehydes are analysed by High Performance Liquid Chromatography- Diode Array Detection (HPLC-DAD) after derivatisation with DNPH and identified by high-resolution MS using an orbitrap-based mass spectrometer. HPLC is the suitable method to investigate the non-volatile aldehydes formed by decomposition of hydroperoxides. The result of this oxidation process were described that the maximum point of the oil oxidation was at 9 hours which peak area 378. For oxidation process at the 10 hours the area peak is decreased which point 344.